Migrations féminines et transformations de l’emploi domestique dans la Bolivie d’Evo Morales - Sophie Blanchard (Les Cahiers ALHIM)
Bolivian women migrate within Bolivia as well as to foreign countries, mostly to Argentina and Spain. Those migrations became an increasing economic resource for the country. Many of these women take jobs as domestic workers. In Spain, working class migrants and middle class migrants share similar experiences and work conditions. In the meantime, in Bolivia a law on domestic workers status was adopted in 2003 and since 2005 Evo Morales’ governments adopted symbolic measures in favor of the domestic workers : domestic workers’ status thus improved. This paper questions the potential relations between the increasing and very diverse women work migrations and the discriminations domestic workers still suffer in Bolivia.